Factors Affecting Destination Selection of Domestic Tourists from Quanzhou city, Fujian Province during COVID-19 - Tan, Shi (Prince of Songkla University, 2023)
Thesis (M.B.A. (Hospitality and Tourism Management))--Prince of Songkla University, 2021